2001
DOI: 10.1088/0967-3334/23/1/306
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dynamic cerebral autoregulation based on spontaneous fluctuations in arterial blood pressure and intracranial pressure

Abstract: Assessments of dynamic cerebral autoregulation usually measure the cerebral blood flow velocity (CBFV) response to changes in arterial blood pressure (ABP). We studied the effect of substituting ABP by cerebral perfusion pressure (CPP), expressed as the difference between ABP and intracranial pressure (ICP), in estimates of dynamic autoregulation obtained by transfer function analysis. CBFV, ABP and ICP were recorded during periods of physiological stability in 30 patients with severe head injury. Transfer fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 35 publications
4
48
0
Order By: Relevance
“…The classical CBFV step response for changes in ABP (Fig. 3) is in very good agreement with previous estimates (9, 11, 29 -31), including studies where ABP was recorded with intravascular catheters (27,32). One interesting consequence of expressing dynamic CA with the linearized model in Fig.…”
Section: Discussionsupporting
confidence: 88%
“…The classical CBFV step response for changes in ABP (Fig. 3) is in very good agreement with previous estimates (9, 11, 29 -31), including studies where ABP was recorded with intravascular catheters (27,32). One interesting consequence of expressing dynamic CA with the linearized model in Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Thus, the question is whether the trauma induces phase shift changes, which interrupt the assumed linearity for coherence found in the controls. Other possible explanations for incongruent results include input power problems 18 ; an inhomogeneous population in which patients without CA disturbances are included with those with loss of CA and the number of investigations for statistical analysis is low; or a loss of linear stability of the system, a condition assumed to be observed by Panerai et al,23 who demonstrated that the system behaved completely differently in TBI patients with ICP Ͼ20 mm Hg compared with TBI patients with ICP Ͻ20 mm Hg. Finally, the impressive phase shift changes must be reconsidered when other mathematical models emerge.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, the pathophysiology of ICH may also involve mechanisms that directly hamper autoregulation, for example, increased intracranial pressure, 24 inflammation response, 25 and edema formation. 24,25 In a pilot study, an invasive assessment was applied to examine autoregulation and brain metabolism in the perihematomal zone of ICH, and a local disturbed autoregulation in edema was recorded.…”
Section: March 2016mentioning
confidence: 99%
“…Undoubtedly, the pathophysiology of ICH may also involve mechanisms that directly hamper autoregulation, for example, increased intracranial pressure, 24 inflammation response, 25 and edema formation. 24,25 In a pilot study, an invasive assessment was applied to examine autoregulation and brain metabolism in the perihematomal zone of ICH, and a local disturbed autoregulation in edema was recorded. 26 Although the hematoma remained stable or was absorbed in the following days, the perihematomal edema always reaches its maximum between 10 and 20 days after ictus, 27 which may explain the more evident autoregulatory dysfunction on days 10 to 12 in our study.…”
Section: March 2016mentioning
confidence: 99%